Miss Peregrine's home for peculiar children : the graphic novel - Riggs, Ransom; Cassandra Jean (New York, NY : Yen Press, 2013)
"A horrific family tragedy sets sixteen-year-old Jacob on a journey to a remote island off the coast of Wales, where he discovers the crumbling ruins of Miss Peregrine's Home for Peculiar Children. As Jacob explores its abandoned bedrooms and hallways, it becomes clear that the children were more than just peculiar. They may have been dangerous. They may have been quarantined on a deserted island for good reason. And somehow--impossible though it seems--they may still be alive"--Publisher's website.
Sequel: Hollow city.
T for teen.
Keywords: Orphanages -- Juvenile fiction; Islands -- Juvenile fiction; Time travel -- Juvenile fiction; Grandfathers -- Juvenile fiction; Orphanages -- Comic books, strips, etc; Islands -- Comic books, strips, etc; Time travel -- Comic books, strips, etc; Grandfathers -- Comic books, strips, etc; Orphanages -- Fiction; Islands -- Fiction; Grandfathers -- Fiction; Supernatural -- Fiction; Wales -- Juvenile fiction; Graphic novels; Detective and mystery fiction